Efficacy and safety of calcineurin inhibitor therapy in lupus nephritis: a systematic review and network meta-analysis - Wu, Yan; Cai, Wenting; Yao, Yao; Zhang, Jinping (Frontiers in Immunology, 2026)
IntroductionThe aim of this study is to compare the efficacy and safety of calcineurin inhibitors in the treatment of lupus nephritis.MethodsWe systematically searched several electronic databases (PubMed, Embase, Cochrane Library, and Web of Science) and the clinical trial registry ClinicalTrials.gov from their inception to March 1, 2025. Our study included randomized controlled trials that enrolled adult lupus nephritis patients receiving calcineurin inhibitors. The outcomes included renal remission rate and incidence of adverse reactions. The network meta-analysis was performed using Stata 14.0.ResultsSixteen randomized controlled trials (with a total of 1994 patients) met the inclusion criteria. Regarding total remission, voclosporin-based triple therapy (mycophenolate mofetil + steroid) ranked highest (surface under the cumulative ranking curve [SUCRA] = 84.3%), followed by tacrolimus-based triple therapy (SUCRA = 78.0%.). For safety outcomes, no statistically significant intergroup differences were observed in adverse events, serious adverse events, or adverse events leading to treatment discontinuation. However, further analysis revealed that voclosporin-based therapy was associated with the highest infection rate (SUCRA = 20.6%), indicating a potential safety concern compared to other regimens; tacrolimus-based therapy had the second-highest infection risk (SUCRA = 27.0%).ConclusionsVoclosporin- and tacrolimus-based triple therapies (both combined with mycophenolate mofetil and steroid) demonstrated high efficacy in lupus nephritis patients. Based on indirect comparisons, the voclosporin regimen appeared to be the most effective. However, it also posed a significantly higher infection risk than other treatments. This underscores that while pursuing high remission rates, vigilant infection monitoring and proactive management are imperative.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero, identifier CRD420251084364.